Preliminary Study on Antifungal Mechanism of Aqueous Extract of Cnidium monnieri Against Trichophyton rubrum - Yanyun, Cao; Ying, Tang; Wei, Kong; Hua, Fang; Haijun, Zhu; Ping, Zheng; Shunming, Xu; Jian, Wan (Frontiers in Microbiology, 2021)
Trichoderma rubrum (T. rubrum) is one of the important pathogens because it is the cause of most dermatomycosis. The treatment of Trichophyton rubrum infection is time-consuming and very expensive; it is easy for the infections to reoccur, leading to therapeutic failures, persistence, and chronic infection. These issues have inspired researchers to study natural alternative therapies instead. Cnidium monnieri (L.), as a kind of traditional Chinese medicine, has a variety of pharmacological activities and a wide range of applications, so it has a high potential for researching and economic value. We detected the effect of aqueous extract of C. monnieri (L.) on the activity of T. rubrum by Cell Count Kit-8 assay (CCK-8), and we found that 128 and 256 μg/ml of aqueous extracts of C. monnieri (L.) co-cultured with T. rubrum for 24 h showed the inhibitory effect on T. rubrum. The results of scanning electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed that aqueous extract of C. monnieri (L.) damaged the T. rubrum. At the same time, mass spectrometry screening with T. rubrum before and after the treatment of 256 μg/ml of aqueous extracts of C. monnieri (L.) showed that 966 differentially expressed proteins were detected, including 524 upregulated differentially expressed genes (DEGs) and 442 downregulated DEGs. The most significantly downregulated protein was chitin synthase (CHS); and the results of qRT-PCR and Western blotting demonstrated that the expression level of CHS was downregulated in the 256 μg/ml group compared with the control group. The study showed that the aqueous extract of C. monnieri (L.) could destroy the morphology of mycelia and the internal structure of T. rubrum, and it could inhibit the growth of T. rubrum. The antifungal effect of aqueous extract of C. monnieri (L.) may be related to the downregulation of the expression of CHS in T. rubrum, and CHS may be one of the potential targets of its antifungal mechanism. We concluded that aqueous extract from C. monnieri (L.) may be a potential candidate for antifungal agents.